Physicochemical Analysis of Subtitution Sus Cake Wheat Flour with Mocaf in a Variation of Peanut Flour : Analisis Fisikokimia Kue Sus Subtitusi Tepung Terigu Dengan Mocaf Pada Variasi Jenis Tepung Kacang - Indah Setiyarini; Vivi Nuraini; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2024)
Eclairs are cakes that are much favored by the general public, became as Ã©clair a hollow texture and are soft on the inside. Mocaf is flour has been modified by fermentation, and has characteristics similar to wheat flour. This reseacrh used a variety of peanuts flour such as cowpeas, red bens and mung beans as protein and fiber source. The variety of nuts added aims to encrease the nutritional content of eclairs. This research was purposed to determine the chemical and sensory characteristics of eclairs which are high in protein and fiber and to determine consumer preferences from the comparison of mocaf and wheat flour with various types of peanut flour. The experimental design used was a Completely Randomized Design (CRD) with two factors, the first factor was the ratio of mocaf flour and wheat flour 9:1, 8:2, 7:3, the second factor was the variety of species of beans, cowpeas, red beans, mung beans. The results showed that the protein content was the highest, in the mocaf and wheat flour of 7:3 with a protein content of 8.50%. the eclairs formulation with the highest fiber content was found in a 9:1 ratio of mocaf flour and wheat flour with variety types of mung beans flour with a fiber content of 9.94%. The formulation of the ratio of mocaf flour : wheat flour 7:3 with variety species is the most preferred formula overall with an overall preference level of 3.67. Eclairs with the addition of peanut flour has the potential to increase product protein.